2001
DOI: 10.21836/pem20010610
|View full text |Cite
|
Sign up to set email alerts
|

A review of the causes of abortion in UK mares and means of diagnosis used in an equine studfarm practice in Newmarket

Abstract: SummaryA retrospective survey of the records of 210 postmortem examinations of aborted equine foeti and placentae, performed at the authors' practice laboratory, revealed that umbilical cord vascular compromise was the most common diagnosis made, accounting for almost 50% of cases. Abortions associated with twin pregnancy now account for a relatively small percentage (2.9%) of cases as compared to much higher incidences (22-29%) seen prior to the introduction of ultrasound scanning and multiple pregnancy reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 7 publications
1
14
0
1
Order By: Relevance
“…A review of the, records of post mortem examinations of 210 preterm (up to 10 months gestation) aborted, predominantly Thoroughbred, fetuses performed by the authors between 1996 and 2001 (Ricketts et al 2001) reported the most common causes. Post mortem examinations were performed on the aborted fetus and, in the majority of cases, umbilical cord and placental membranes, usually on the same day or the day after the abortus was found by stud staff.…”
Section: Causes Of Abortionmentioning
confidence: 98%
See 1 more Smart Citation
“…A review of the, records of post mortem examinations of 210 preterm (up to 10 months gestation) aborted, predominantly Thoroughbred, fetuses performed by the authors between 1996 and 2001 (Ricketts et al 2001) reported the most common causes. Post mortem examinations were performed on the aborted fetus and, in the majority of cases, umbilical cord and placental membranes, usually on the same day or the day after the abortus was found by stud staff.…”
Section: Causes Of Abortionmentioning
confidence: 98%
“…Surveys of the causes of abortions, stillbirths and neonatal losses have been published over the years, from different parts of the world (Mahaffey 1968;Bain 1969;Prickett 1970;Platt 1973Platt , 1975Platt , 1979Dimmock et a/. 1974;Rossdale and Ricketts 1976;Whitwell 1980;Acland 1993;Ricketts et a/. 2001).…”
Section: Introductionmentioning
confidence: 99%
“…1987). Before ultrasound scanning for pregnancy became widespread, twin pregnancy was the most important cause of abortion diagnosed in UK, whereas twin pregnancy is now seldom seen and umbilical cord torsion, often associated with a long umbilical cord, is now the most important cause in the UK (Ricketts et al . 2001; Smith et al .…”
Section: Incidence Of Equine Perinatal Losses and Importance Of Diagnmentioning
confidence: 99%
“…In recent years some interesting observations have been made on the changing aetiology of abortion in mares (Ricketts et al 2001;Smith et al 2003;Williams et al 2003). The incidence of twin abortions has dropped significantly due to early intervention after ultrasonographic diagnosis of a multiple pregnancy.…”
mentioning
confidence: 99%
“…Reports from the UK suggest that with the decline in twin abortions, excessive twisting of the umbilical cord has become the most frequently made diagnosis in some laboratories. These abortions were associated with excessively long cords, with many over 80 cm in length (Ricketts et al 2001;Smith et al 2003). Since spiralling of the equine cord (4-5 times over its length) is a normal feature (Fig 1a), it is important to ensure that the cause of fetal demise was in fact due to vascular compromise (Vandeplassche and Lauwers 1986;Schlafer 2003).…”
mentioning
confidence: 99%